Localization of mobile using RSS and Hilbert-Huang transform - Jyothirma, V; N.V.K Ramesh, Dr; Navyateja, Y; Vijay, R (International Journal of Engineering and Technology, 2018)
Mobile navigation has drawn much attention in multitudinous application. However, operational capability of mobile degrades due to buildings and dense foliage. The proposed methods like ‘RSS mobile estimation using wavelets’ are designed for detecting the mobile location for different outdoor environments. This paper presents deciphers the subtleties involved in the application of EMD and Hilbert-Huang Transform approach applied for collected rural and urban data for mobile localization possible even in indoor scenario. By experimental results shown the variations in signal strength due to the distance travelled by the mobile.
Keywords: Mobile Navigation; H-H Transform; EMD; RSS; Signal Strength Estimation.